ANALISIS BIBLIOMETRIK PERAN BAHASA DALAM KOMUNIKASI PEMBELAJARAN MATEMATIKA TERHADAP HASIL BELAJAR PESERTA DIDIK - Wulandari, Dyah Ayu; Soebagyo, Joko (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
Mathematics is an abstract subject so it is considered a difficult subject for some students and students. Language is a human communication tool. The use of language that is well structured and precise will make it easier for the interlocutor to understand what is being conveyed, this also applies in learning. The level of students' understanding of the material presented by educators is the main factor that can affect student learning outcomes. The method used in this research is bibliometric analysis method. Bibliometric analysis is a research method used by researchers to find the widest possible information related to keywords in the research to be carried out. The objectives of this research are, among others: (1) To find out trends regarding language research in mathematics learning communication. (2) To find out the great opportunities for further research on the topic of language in mathematics learning communication. The researcher found that there have been many studies with the keyword “mathematics”, but there is still little research related to mathematics learning, mathematics outcomes and quality. This can be an opportunity for further research to conduct research on these three keywords.